Лазер на парах меди со стабилизацией выходных характеристик - Евтушенко Г. С. Геннадий Сергеевич; Воронов В. И.; Егоров А. Л.; Карманов Г. А.; Мальцев А. Н.; Федоров В. Ф.; Филонов А. Г.; Юдин Н. А. (1986, 1986)
В фонде НТБ ТПУ отсутствует